COMPARATIVE CHARACTERISTICS OF THE AVAILABLE LABORATORY TESTS AND THEIR COMBINATIONS USED IN DIFFERENTIAL DIAGNOSIS OF OVARIAN NEOPLASMS - M. A. Egunova; I. G. Kutsenko (Акушерство, гинекология и репродукция, 2018)
n the case of a space-occupying lesion (SOL) of the ovary, it is up to the gynecologist to diagnose a possible malignancy and then decide upon further treatment strategy. The aim of the study was to perform a comparative analysis of the existing methods for detecting the tumor markers: CA-125 – cancer antigen 125 and HE4 – human epididymis protein 4. We also compared the prognostic indices (Risk Malignancy Index – RMI and Risk of Ovarian Malignancy Algorithm – ROMA) currently used to make differential diagnoses of benign and malignant ovarian neoplasms at the preoperative stage. Materials and methods. We conducted a prospective study in 100 patients from 18 to 79 years old scheduled for surgery for an ovarian SOL. The serum levels of the CA-125 and HE4 tumor markers, pelvic sonography, the RMI and ROMA scores, as well as post-surgery histopathology results were evaluated. Results. The sensitivities of the CA-125, HE4, RMI and ROMA indices were 85.7%, 42.9%, 85.7% and 71.4%, respectively; the values of specificity were 83.6%, 97.8%, 96.7%, 97.8%, respectively. Conclusion. The most informative parameter for the differential diagnosis of benign and malignant ovarian neoplasms at the preoperative stage was the RMI, and the least informative – the HE4 tumor marker. The HE4 determination was highly informative, however, in the differential diagnosis of ovarian malignant neoplasms with endometrioid cysts in patients with elevated CA-125 levels. Notably, patients with widespread external genital endometriosis showed false-positive results of the CA-125, HE4, RMI and ROMA tests. In a patient with clear-cell ovarian carcinoma, the sensitivity and specificity of the CA-125, HE4, RMI, and ROMA tests were confirmed to be low.